Investigation of Li+ insertion in columbite structured FeNb2O6 and rutile structured CrNb2O6 materials. (20th January 2015) - Samarasingha, Pushpaka B.; Thomas, Chris I.; Fjellvåg, Helmer
Graphical abstract: Highlights: FeNb2 O6 and CrNb2 O6 cathode materials achieved. Reversible lithium insertion proved in both FeNb2 O6 and CrNb2 O6 . Nb(V)/Nb(IV) redox couple dominant rather than Cr(III)/Cr(II). Initial drop in capacity interpreted as a result of channel blocking. Strategies for future material developments proposed. Abstract: Lithium insertion in FeNb2 O6 and CrNb2 O6 has been investigated using the galvanostatic charge–discharge method and showed that more than half of the intercalated Li + during first cycle is retained in the structure and is not de-intercalated during subsequent cycles. The effects of sintering on FeNb2 O6 were investigated with lower applied temperatures yielding higher Li + intercalation capability. Post galvanostatic XRD shows that the initial phase has been retained during cell cycling. Cyclic voltammetry reveals that chromium also takes part in electro-chemical activity in CrNb2 O6 .